Assessment of the flow-diverter efficacy for intracranial aneurysm treatment considering pre- and post-interventional hemodynamics. (April 2023) - Stahl, Janneck; Marsh, Laurel Morgan Miller; Thormann, Maximilian; Ding, Andreas; Saalfeld, Sylvia; Behme, Daniel; Berg, Philipp
Abstract: Endovascular treatment of intracranial aneurysms with flow diverters (FD) has become one of the most promising interventions. Due to its woven high-density structure they are particularly applicable for challenging lesions. Although several studies have already conducted realistic hemodynamic quantification of the FD efficacy, a comparison with morphologic post-interventional data is still missing. This study analyses the hemodynamics of ten intracranial aneurysm patients treated with a novel FD device. Based on pre- and post-interventional 3D digital subtraction angiography image data, patient-specific 3D models of both treatment states are generated applying open source threshold-based segmentation methods. Using a fast virtual stenting approach, the real stent positions available in the post-interventional data are virtually replicated and both treatment scenarios were characterized using image-based blood flow simulations. The results show FD-induced flow reductions at the ostium by a decrease in mean neck flow rate (51%), inflow concentration index (56%) and mean inflow velocity (53%). Intraluminal reductions in flow activity for time-averaged wall shear stress (47%) and kinetic energy (71%) are present as well. However, an intra-aneurysmal increase in flow pulsatility (16%) for the post-interventional cases can be observed. Patient-specific FD simulations demonstrate the desired flow redirection and activity reduction inside the aneurysm beneficial for thrombosis formation. Differences in the magnitude of hemodynamic reduction exist over the cardiac cycle which may be addressed in a clinical setting by anti-hypertensive treatment in selected cases. Highlights: Pre- and post-interventional intracranial aneurysm models are considered for virtual flow diverter deployment. The extraction of patient-specific flow diverter geometry from imaging data improves realistic virtual stenting results. Time-dependent hemodynamic simulations show intra-aneurysmal shear and flow reduction by the deployed flow diverters. Flow diversion is more effective during diastole compared to systole.